ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN CAKUPAN IMUNISASI DASAR LENGKAP DI BAITUSSALAM, ACEH BESAR - Suliawati, Gidul; Usman, Said; Maulana, Teuku; Saputra, Irwan; Zaman, Nasrul (Universitas Udayana, 2023)
The immunization program is included in efforts to reduce morbidity, disability and death in infants and toddlers. Complete Basic Immunization Coverage in Aceh Besar District has decreased every year, atleast is still below the national target of 85%. This study aims to determine the factors associated with complete basic immunization coverage at the Baitussalam Health Center in 2022. This research was conducted using a quantitative study with a cross-sectional approach with data collection using a questionnaire and analyzed univariately to describe the distribution and proportions, as well as bivariate using Chi Square and using multivariate analysis with linear regression. Result of the study showed more than half (57.4%) of mothers did not give complete immunization to their babies. This study found that there was a relationship between the provision of complete basic immunization and the mother's employment status (p value = 0.018), level of knowledge (p value = 0.484), family support (p value = 0.000), mother's trust (p value = 0.000). The most dominant factors affecting complete basic immunization coverage at the Baitussalam are factors of knowledge, trust, the role of health workers and health cadres.